EFEKTIVITAS PEMUNGUTAN PAJAK PROGRESIF TERHADAP PENDAPATAN ASLI DAERAH PADA KANTOR SAMSAT KOTA MAKASSAR - Yulianti Yulianti; Mursalim Mursalim; Muh. Su’un (Jurnal Riset Perpajakan: Amnesty, 2021)
This study aims to determine the effectiveness of progressive tax collection on local revenue at the Samsat Office for Makassar 1 Selatan Region. This research is descriptive qualitative. The types of data used are primary data and secondary data. Collecting data using observation, interview and literature techniques. The results of this study indicate that the collection of Progressive Motor Vehicle Taxes has been very effective in the period 2016 to 2018 and has a very significant impact on Regional Original Income.